Effect of social support systems in the treatment processes and motivation of individuals addicted to alcohol/substance - Acar, Burak; Çakır, Gamze; Karaköse, Şeymanur; Yaman, Ömer Miraç (Journal of Dependence, 2022)
Objective: The aim of the study is to discover the importance of the social support system in the initiation or continuation of the treatment of individuals addicted to alcohol and substance. Method: In this context, in-depth interviews and observations have been made using the qualitative research method with 18 addicted participants who are in their treatment processes, and the data that have been obtained were analyzed with the descriptive analysis method. Results: It has been detected that social support affects the decision to get the treatment, the motivation to continue the treatment, staying sober for longer, and the treatment having a positive course. It has been determined that there is a close correlation between the prolongation of the remission period of addicts and their social support systems. Family, friends, self-help groups, religious beliefs and work life stand out as the social systems that provide the most support for the participants in the treatment process. Conclusion: In addition to psychological or medicated treatment methods, especially the processes of making a decision about the treatment and maintaining the treatment should be managed professionally. It is considered to be important to increase the approaches and methods that will enable working closely with the social systems of the addicted individuals in order to increase the success in the treatment of addiction.